Assessment of Reliability of the Transport Information Systems - Boris Zhelenkov; Irina Safonova; Yakov Goldovsky; Alexander Abramov; Nataliya Tsyganova (Communications - Scientific letters of the University of Zilina, 2022)
In this paper is given the definition of e reliability of a transport information system, with features of transport information systems listed. Equations for calculating reliability indicators are given, as well. The developed hierarchical graph model for assessing the reliability of transport information systems and an algorithm for analyzing the graph model, which allows taking into account the specifics of the reliability of the operation of system elements at different levels of the hierarchy, are presented. Using the graph model and the graph model analysis algorithm, it is possible to reasonably predict the strategy for the creation and development of transport information systems.